Gustatory alteration evaluation in patients with chronic otitis media Avaliação de alteração gustatória em pacientes com otite média crônica - Felippe Felix (Brazilian Journal of Otorhinolaryngology, 2009)
Many studies have shown the consequent gustatory alteration caused by ear surgeries. However, few have reported this alteration in patients with chronic otitis media (COM), prior to surgical treatment. AIM: to identify gustatory alterations due to chorda tympani nerve involvement in patients with COM without prior surgery. METHODS: Clinical essay, with tests based on "taste strips" with different concentrations of salt, sweet, bitter, and sour, was performed in 45 patients with unilateral cholesteatomatous or suppurated COM not previously submitted to otological surgery, using the disease-free ear on the contralateral side as control. The score ranged between 0 and 16. RESULTS: A total of 25 patients presented cholesteatoma and 20 had non-cholesteatomatous disease. The mean score was 6.65 for the affected side and 9.93 for the half of the tongue on the side of the healthy ear (p<0.001). No patients had complained of gustatory alterations before the examination. Among the 24 patients with unilateral hypogeusia, eight cases of unilateral ageusia were found on the affected side. There was an association between cholesteatoma (p=0.055), disease duration (p=0.07) and worsening in gustatory sensitivity. CONCLUSION: Patients with COM can have gustatory alterations, even in the absence of complaints. Muitos estudos mostraram a consequente alteração do paladar após cirurgia otológica. Entretanto, poucos reportaram essa alteração como uma queixa de pacientes com otite média crônica (OMC) previamente à cirurgia. OBJETIVO: Avaliar alterações na função gustatória na área inervada pelo nervo corda do tímpano em pacientes com OMC ainda não submetidos à cirurgia. MATERIAL E MÉTODOS: O ensaio clínico, com teste gustatório baseado em "tiras gustativas" com diferentes concentrações de sal, doce, amargo e azedo, foi realizado em 45 pacientes com OMC colesteatomatosa e não-colesteatomatosa unilateral, nunca antes submetidos à cirurgia otológica, utilizando a metade da língua do lado livre de doença otológica como controle. As notas variavam de 0 a 16. RESULTADOS: 25 pacientes apresentavam colesteatoma e o restante OMC não-colesteatomatosa. A pontuação média foi de 6,65 para o lado afetado e 9,93 para a metade da língua do lado sadio (p<0,001). Nenhum paciente se queixava de alteração do paladar antes do exame. Encontramos 24 casos de hipogeusia do lado afetado, sendo 8 (17,7%) casos de ageusia. Houve uma relação entre tempo de doença (p=0,07) e colesteatoma (p=0,055) com piora da sensibilidade gustativa. CONCLUSÃO: Pacientes com OMC podem apresentar alteração gustativa, mesmo na ausência de queixas.